Pengaruh Kepribadian, Lingkungan Keluarga dan Pelatihan Kewirausahaan terhadap Aktivitas Berwirausaha Alumnus Lembaga Pelatihan Kerja ( LPK ) Citarum Motor Nganjuk - Tulus Candra Susila; Suwandi Suwandi (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2019)
This study aims to find out (1) the influence of the personality of the Entrepreneurship activity against alumnus LPK CITRUM MOTOR.(2) the influence of the family environment towards Entrepreneurship activity alumnus LPK CITRUM MOTOR, (3) the influence of entrepreneurial training towards Entrepreneurship activity alumnus LPK CITRUM MOTOR, (4) and the influence of the Family Environment, Personality, and training Entrepreneurship Entrepreneurship activity against alumnus LPK CITRUM MOTOR. This includes research into causal research is associative. The population in this research is a work training Institute alumnus 239 2014, 2015 and 2016 with sample research as many as 139 people.The technique of sampling with proportional random sampling. Data collection techniques used are questionnaire.Test of normality tests include analysis of the prerequisites, test linearity, multicollinearity test, and test heteroskedastisitas.Analytical techniques the analysis of data with simple linear regression and multiple linear regression.